Complete Village [Sub-District] Development Acceleration Strategy in Sukun District, Malang City - Na'Afi, Ramadhani Naufal; Suharto, Eko; Widiyantoro, Susilo (Sekolah Tinggi Pertanahan Nasional, 2025)
The development of a complete city/regency is a strategic agenda of the Ministry of ATR/BPN to realize legal certainty over land. Malang City has achieved Complete City status, but the implementation of the Complete Village development in Sukun District still faces various obstacles. This issue is important to study because success at the village level is a benchmark for the quality of national land policy implementation. This study aims to analyze the implementation, problems, and strategies for accelerating the development of Complete Villages after the declaration of Complete City 2024. The study used a descriptive qualitative method with data collection techniques through structured interviews, field observations, and document reviews. Data were analyzed descriptively using the Miles and Huberman model with the application of three analytical tools: the 5M management approach (man, money, material, machine, method) to assess internal factors, Rumelt's Evaluation Theory to measure consistency, suitability, excellence, and feasibility of strategies, and SWOT Analysis to formulate adaptive strategies. The results indicate that the development of Complete Villages in Sukun District follows four main stages according to the 2022 PTSL Technical Guidelines and has fulfilled the 5M elements. However, Rumelt's evaluation identified technical and non-technical constraints, such as limited technological infrastructure, human resource capacity, and inter-agency coordination. The SWOT analysis recommended strategies such as strengthening institutional vision, improving cross-sectoral coordination, collaborating with third parties, and utilizing digital technology, particularly Artificial Intelligence (AI), to accelerate the sustainable implementation of the Complete Village.